Measurement report: Spatial variations in ionic chemistry and water-stable isotopes in the snowpack on glaciers across Svalbard during the 2015–2016 snow accumulation season - E. Barbaro; E. Barbaro; K. Koziol; M. P. Björkman; C. P. Vega; C. P. Vega; C. Zdanowicz; T. Martma; J.-C. Gallet; D. Kępski; C. Larose; B. Luks; et al. (Atmospheric Chemistry and Physics, 2021)
The Svalbard archipelago, located at the Arctic sea-ice edge between 74 and 81∘ N, is ∼60 % covered by glaciers. The region experiences rapid variations in atmospheric flow during the snow season (from late September to May) and can be affected by air advected from both lower and higher latitudes, which likely impact the chemical composition of snowfall. While long-term changes in Svalbard snow chemistry have been documented in ice cores drilled from two high-elevation glaciers, the spatial variability of the snowpack composition across Svalbard is comparatively poorly understood. Here, we report the results of the most comprehensive seasonal snow chemistry survey to date, carried out in April 2016 across 22 sites on seven glaciers across the archipelago. At each glacier, three snowpits were sampled along the altitudinal profiles and the collected samples were analysed for major ions (Ca2+, K+, Na+, Mg2+, <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3226c502fdca30fe88bf9305df4b3716"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00001.svg" width="24pt" height="15pt" src="acp-21-3163-2021-ie00001.png"/></svg:svg>, <msubsup>SO42-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="29pt" height="17pt" class="svg-formula" dspmath="mathimg" md5hash="40da026c69d6bb7b362f8aefb7758b92"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00002.svg" width="29pt" height="17pt" src="acp-21-3163-2021-ie00002.png"/></svg:svg>, Br−, Cl−, and <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="eb51cd45ba2a21283d090226a04e61ba"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00003.svg" width="25pt" height="16pt" src="acp-21-3163-2021-ie00003.png"/></svg:svg>) and stable water isotopes (δ18O, δ2H). The main aims were to investigate the natural and anthropogenic processes influencing the snowpack and to better understand the influence of atmospheric aerosol transport and deposition patterns on the snow chemical composition. The snow deposited in the southern region of Svalbard is characterized by the highest total ionic loads, mainly attributed to sea-salt particles. Both <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="c5e3e0772eea57309f236de17ca43cb8"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00004.svg" width="25pt" height="16pt" src="acp-21-3163-2021-ie00004.png"/></svg:svg> and <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="8954cfb2fcef1f8dc372e5d7425e25d0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00005.svg" width="24pt" height="15pt" src="acp-21-3163-2021-ie00005.png"/></svg:svg> in the seasonal snowpack reflect secondary aerosol formation and post-depositional changes, resulting in very different spatial deposition patterns: <msubsup>NO3-</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="25pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="48a6d5724cc017ced9c974ab9a81c03a"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00006.svg" width="25pt" height="16pt" src="acp-21-3163-2021-ie00006.png"/></svg:svg> has its highest loading in north-western Spitsbergen and <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="8b20487e53d7ab6a3bf592e9df90e3eb"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-21-3163-2021-ie00007.svg" width="24pt" height="15pt" src="acp-21-3163-2021-ie00007.png"/></svg:svg> in the south-west. The Br− enrichment in snow is highest in north-eastern glacier sites closest to areas of extensive sea-ice coverage. Spatial correlation patterns between Na+ and δ18O suggest that the influence of long-range transport of aerosols on snow chemistry is proportionally greater above 600–700 m a.s.l.